Attitude and Interest of Dentists and Dental Patients Towards Teledentistry Services for Oral Healthcare Management Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Oral health is an integral part of our overall health and well-being but it is regularly ignored in the healthcare delivery system in Bangladesh. A few significant factors are the general public's lack of awareness and the shortage of infrastructure and resources like dentists and specialists. Due to the COVID-19 pandemic, the condition is more critical. Many countries are practicing Teledentistry (Smartphone- based digital platform) services which could be an alternative for Oral Health Care Management in Bangladesh both for the urban and rural people. So, the aim of this study was to assess the attitude and interest of dentists and dental patients in Bangladesh towards Teledentistry which is a technology-based digital platform for oral health care management. Materials and methods: This cross-sectional study was conducted during the period from July - December 2021 using a pretested semi-structured questionnaire for dental patients. An online questionnaire was sent to 300 participants of both rural and urban people of Bangladesh and 206 responded. The response rate was 68%. For dentists we used a qualitative approach, we conducted a focus group discussion at Dhaka Dental College Hospital among a group of dentists. Results: The findings of this study showed that 82.7% of dental patients were highly interested in teledentistry for use in the future if available in our country and 74.3% of them were not satisfied with present oral and dental service-taking procedures. At the same time, the majority of the dentists showed a positive attitude and interest towards Teledentistry service in Bangladesh and they expressed that it will be an amazing initiative for our country which is the need of time now. Conclusion: So, the findings of this study assessed the attitudes and interests of dentists and dental patients which will help in the future development of smartphone phone-based teledentistry platform in Bangladesh.Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 84-89